A Rationality Study of Antihypertensive Drugs Usage in Preeclampsia Patients in the Private Hospital - Wijaya, Dhani; Rohmah, Afwa Syahara; Syarifuddin, Sadli; Rahmadanita, Fathia Faza (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2023)
Preeclampsia is a hypertension that happens in pregnancy of ≥ 20 weeks and occurs with proteinuria. Preeclampsia is also the highest cause of mother’s death second place in Indonesia. According to that, a study of rationality is needed concerning medicine usage as one of the efforts to determine which medicine is accepted by the rational patient so that the expected therapeutic effect is achieved and does not harm the lives of the mother and baby. The purpose of this research is to determine the profile and rationality of anti-hypertension medicine usage on pregnant mothers with preeclampsia at a private hospital in Malang. This is an observational descriptive research that uses retrospective data. The sample-taking method of this research is using a total sampling method. This research data is served on a diagram or table and percentage. The result of this research is that 3 kinds of anti-hypertension medicine are used: nifedipine 78%, amlodipine 17%, and candesartan 5%. The rationality study of the use of antihypertensive drugs in this study obtained 78% correct indication, 100% correct drug, 93% correct dose, 62% correct interval of administration, and 100% correct patient. This study shows that the usage of antihypertensive drugs in preeclampsia is rational in several parameters.